2016
DOI: 10.18632/oncotarget.10103
|View full text |Cite
|
Sign up to set email alerts
|

FOXM1 promotes reprogramming of glucose metabolism in epithelial ovarian cancer cells via activation of GLUT1 and HK2 transcription

Abstract: Cancer cells exhibit the reprogrammed metabolism mainly via aerobic glycolysis, a phenomenon known historically as the Warburg effect; however, the underlying mechanisms remain largely unknown. In this study, we characterized the critical role of transcription factor Forkhead box protein M1 (FOXM1) in aerobic glycolysis of human epithelial ovarian cancer (EOC) and its molecular mechanisms. Our data showed that aberrant expression of FOXM1 significantly contributed to the reprogramming of glucose metabolism in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 48 publications
(43 reference statements)
0
38
0
Order By: Relevance
“…In addition, to fuel cancer cell growth and malignancy, cancer cells could alter some oncogentic gene (MYC, IDH1, kRas) abnormal expressions, subsequently, increase Glut1 expression and accelerate glucose uptake and process of anabolic glucose metabolism [Flier et al, 1987;Dang et al, 2009;Ying et al, 2012;Boroughs and DeBerardinis, 2015]. Furthermore, FOXM1 (Forkhead box protein M1) could promote reprogramming of glucose metabolism via inducing Glut1 expression [Wang et al, 2016]. The deprivation of glucose triggers the K-Ras mutation and Glut1 expression that could enhance glucose uptake and cell survival in low-glucose conditions [Yun et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, to fuel cancer cell growth and malignancy, cancer cells could alter some oncogentic gene (MYC, IDH1, kRas) abnormal expressions, subsequently, increase Glut1 expression and accelerate glucose uptake and process of anabolic glucose metabolism [Flier et al, 1987;Dang et al, 2009;Ying et al, 2012;Boroughs and DeBerardinis, 2015]. Furthermore, FOXM1 (Forkhead box protein M1) could promote reprogramming of glucose metabolism via inducing Glut1 expression [Wang et al, 2016]. The deprivation of glucose triggers the K-Ras mutation and Glut1 expression that could enhance glucose uptake and cell survival in low-glucose conditions [Yun et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study and our recent publication demonstrated that a key glycolytic transporter, glucose transporter 1 (GLUT1), is specifically overexpressed in HCC and promotes HCC cell glycolysis and progression (Amann et al , 2009; Shang et al , 2017). We further revealed that GLUT1 is transactivated by the transcription factor Forkhead box M1 (FOXM1) in different cancer types (Shang et al , 2017; Wang et al , 2016). However, knowledge of how noncoding genes regulate GLUT1 expression is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest that promotion of glycolysis triggers tumor metastasis in HCC cell lines. HK2, a rate‐determining enzyme in aerobic glycolysis, is overexpressed in many cancer types, including glioblastoma multiforme, lung cancer, and ovarian cancer . Further, the regulation of HK2 is mediated by lncRNA urothelial cancer‐associated 1, miRNA, or epigenetic alterations .…”
Section: Discussionmentioning
confidence: 99%